The Influence of Corporate Social Responsibility on Financial Performance with Profit Management as a Moderating Variable - Made Ani Setia Wulan; Anak Agung Gede Putu Widanaputra; I Ketut Yadnyana (Budapest International Research and Critics University, 2022)
The company's financial performance can be used as a benchmark that shows the company's condition in good or bad condition. Company performance can be increased by implementing corporate social responsibility. Earnings management arises due to the asymmetry between management and owners which provides opportunities for managers to act opportunistically.This study aims to obtain empirical evidence regarding the effect ofcorporate social responsibility on financial performance moderated by earnings management. The research sample is 68 manufacturing companies in the consumer goods industry sector which are registered in IndonesiaIndonesia stock exchangeperiod 2018-2019. The method of determining the sample, namely, purposive sampling method and data collection usingnon-participant observation method. Data analysis techniques usingModerated Regression Analysis (MRA) using Statistical Product and Service Solution (SPSS). Based on the results of the analysis, it shows that there is a positive and significant influence between CSR on the financial performance of manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange for the 2018-2019 period. The analysis of the moderating variables shows that earnings management cannot strengthen or weaken the relationship between CSR and financial performance. The implications of this research arecompanies need to formulate strategies in disclosing CSR. For potential investors and investors the results of this study can be used as material for consideration in making investment decisions through the disclosure of CSR information carried out by the company.